Desenvolvimento de geopolímeros utilizando materiais de baixo custo visando a melhoria das propriedades de ligante asfáltico - Freitas, Armando Diego Lima de (2023)
The Earth has been facing serious consequences caused by the excessive presence of CO2 in the atmosphere. As a result, reducing emissions has become an urgent global issue, demanding a societal change in environmental resource management, particularly in the cement and asphalt industries that rely on fossil fuels, responsible for the largest release of polluting gases. Consequently, the production of materials derived from renewable sources or industrial waste has become imperative. This study aims to develop geopolymers (GP), inorganic polymers composed of aluminosilicates, using coal fly ash (FA) and kaolin, and to assess their potential as additives in asphalt binder (AB). For the application of FA as industrial residues, a physicochemical separation treatment was employed to remove materials that could potentially interfere with GP synthesis. The GP synthesis involved six Si/Al oxide ratios ranging from 2.0 to 4.5, with curing times of 7, 14, 21, and 28 days. Analysis using FTIR, SEM, and TG confirmed the presence of interatomic bonding bands in the obtained materials, indicating a particular morphology and temperature resistance. Thermal analysis results revealed that water retention in GP pores occurred at approximately 16 wt.%, suggesting its potential as an additive in Warm Mix Asphalt (WMA), as demonstrated with asphalt binder (AB) modified with G4.0 at 2.4, 6, and 8% of geopolymers. Concerning mechanical properties, compressive strength analysis of the G4.5_28 sample showed the highest strength at 19.92 MPa. N2 physisorption tests exhibited Type II isotherms, suggesting a mesoporous material with an average pore width less than 4.5 nm. Empirical and Brookfield viscosity tests for modified asphalt binders aligned with current specifications. Rheological results showed no differences in stiffness (G*) of the modified AB with GP but suggested an increase in elasticity (δ). The MSCR test at 58 °C presented parameters in compliance with normative requirements, and storage stability tests did not show phase separation. Comparative adhesion tests revealed better aggregate coverage with binders modified with GP. Geopolymers were efficiently synthesized and demonstrated potential for application in the production of Warm Mix Asphalt. Characteristics such as porosity and compressive strength suggest that GPs also have potential for use as adsorbents for gases and metal ions in aqueous solutions.